Enhancing Students’ Understanding of RA (Religious Affairs) through Interactive Learning at Salman Sarif Hidayatullah - Irma Rismawati; Aan Nurjanah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students’ understanding of Religious Affairs (RA) at Salman Sarif Hidayatullah through the implementation of interactive learning strategies. Religious Affairs, as a critical aspect of Islamic education, require students to not only memorize religious laws but also to understand their application in daily life. Traditional teaching methods often focus on passive learning, where students are primarily recipients of information, which limits their ability to engage critically with the material. This research explores how interactive learning, which involves active student participation through discussions, case studies, and practical examples, can enhance students’ comprehension and interest in RA. The study was conducted in two cycles, involving 10th-grade students at Salman Sarif Hidayatullah. In each cycle, students participated in interactive learning activities, including group discussions, role-plays, and problem-solving exercises based on real-life scenarios related to RA topics. Data were collected through observations, student surveys, and pre- and post-tests to measure improvements in student engagement, understanding, and the application of RA principles. The findings indicate that interactive learning significantly improved students’ understanding of RA. Students became more engaged in the learning process, asking relevant questions, sharing their ideas, and discussing how RA concepts applied to their lives. Furthermore, students showed increased confidence in applying religious principles to real-life situations, suggesting that interactive learning fosters a deeper and more practical understanding of RA. This research concludes that interactive learning is an effective method for enhancing students’ comprehension of Religious Affairs and creating a more dynamic, student-centered learning environment.